Tannic Acid-Modified Silver and Gold Nanoparticles as Novel Stimulators of Dendritic Cells Activation - Orlowski, Piotr; Tomaszewska, Emilia; Ranoszek-Soliwoda, Katarzyna; Gniadek, Marianna; Labedz, Olga; Malewski, Tadeusz; Nowakowska, Julita; Chodaczek, Grzegorz; Celichowski, Grzegorz; Grobelny, Jaroslaw; Krzyzowska, Malgorzata (Frontiers in Immunology, 2018)
Silver nanoparticles (AgNPs) are promising new antimicrobial agents against a wide range of skin and mucosal pathogens. However, their interaction with the immune system is currently not fully understood. Dendritic cells (DCs) are crucial during development of T cell-specific responses against bacterial and viral pathogens. We have previously shown that tannic acid-modified silver nanoparticles (TA-AgNPs) consist of a promising microbicide against HSV-2. The aim of this study was to compare the ability of TA-AgNPs or TA-AuNPs of similar sizes (TA-Ag/AuNPs) to induce DCs maturation and activation in the presence of HSV-2 antigens when used at non-toxic doses. First, we used JAWS II DC line to test toxicity, ultrastructure as well as activation markers (MHC I and II, CD40, CD80, CD86, PD-L1) and cytokine production in the presence of TA-Ag/AuNPs. Preparations of HSV-2 treated with nanoparticles (TA-Ag/AuNPs-HSV-2) were further used to investigate HSV-2 antigen uptake, activation markers, TLR9 expression, and cytokine production. Additionally, we accessed proliferation and activation of HSV-2-specific T cells by DCs treated with TA-AgNP/AuNPs-HSV-2. We found that both TA-AgNPs and TA-AuNPs were efficiently internalized by DCs and induced activated ultrastructure. Although TA-AgNPs were more toxic than TA-AuNPs in corresponding sizes, they were also more potent stimulators of DCs maturation and TLR9 expression. TA-Ag/AuNPs-HSV-2 helped to overcome inhibition of DCs maturation by live or inactivated virus through up-regulation of MHC II and CD86 and down-regulation of CD80 expression. Down-regulation of CD40 expression in HSV-2-infected DCs was reversed when HSV-2 was treated with TA-NPs sized >30 nm. On the other hand, small-sized TA-AgNPs helped to better internalize HSV-2 antigens. HSV-2 treated with both types of NPs stimulated activation of JAWS II and memory CD8+ T cells, while TA-AgNPs treatment induced IFN-γ producing CD4+ and CD8+ T cells. Our study shows that TA-AgNPs or TA-AuNPs are good activators of DCs, albeit their final effect upon maturation and activation may be metal and size dependent. We conclude that TA-Ag/AuNPs consist of a novel class of nano-adjuvants, which can help to overcome virus-induced suppression of DCs activation.